2012
DOI: 10.1111/j.1470-6431.2012.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Fashion consumer groups and online shopping at private sale sites

Abstract: With the increasing popularity of private sale sites, it has become more important to understand those shoppers regularly visiting these sites. To date, no published studies have reported on shoppers of private sale sites. The current study was designed to divide shoppers of private sale sites into distinct fashion consumer groups based on their levels of fashion leadership, and to examine their differences in shopping behaviours. Data were collected from a convenience sample of 164 women aged 18 and older who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…In a study of fashion consumers who shop from private sale sites, the respondents are divided into four groups, fashion followers, fashion opinion leaders, fashion innovators and innovative communicators. The results show that innovative communicators have signifi cantly higher levels of visit frequency and purchase intention (Kim and Martinez 2013 ). A study of online auction fi nds that there are distinct auction shopper segments based on adventure and gratifi cation shopping motivations.…”
Section: Consumer Behavior In Online Shoppingmentioning
confidence: 98%
“…In a study of fashion consumers who shop from private sale sites, the respondents are divided into four groups, fashion followers, fashion opinion leaders, fashion innovators and innovative communicators. The results show that innovative communicators have signifi cantly higher levels of visit frequency and purchase intention (Kim and Martinez 2013 ). A study of online auction fi nds that there are distinct auction shopper segments based on adventure and gratifi cation shopping motivations.…”
Section: Consumer Behavior In Online Shoppingmentioning
confidence: 98%
“…Some researchers state that the consumers who are personally innovative and seek newness will prefer to use these platforms for shopping (Baybars & Ustundagli, 2011). The private sale sites offer the products for a specific period of time without allowing the consumers to know what will be sold (Kim & Martinez, 2013). It is reported that limited time format allows consumers to do the shopping for a limited period of time and it enables the customers to get a preview of what is going to be offered by enticing an appetite for luxury goods (Martinez, 2011).…”
Section: Literature Review On Technology Acceptance Modelmentioning
confidence: 98%
“…It is reported that limited time format allows consumers to do the shopping for a limited period of time and it enables the customers to get a preview of what is going to be offered by enticing an appetite for luxury goods (Martinez, 2011). Kim and Martinez (2013) add that the private sale sites presented a unique shopping experience through exclusive membership which provides a special treatment such as being able to start their shopping earlier than the rest for the premium members that are loyal customers and frequent shoppers.…”
Section: Literature Review On Technology Acceptance Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Both can be artificially managed online with social sharing facilities and reduced offering. Innovative communicators have been found more likely than fashion followers to visit private sales sites frequently and purchase from them (Kim & Martinez, 2013). They are looking after bargain and after sharing their good experience, their smart shopping.…”
Section: Opsrs and Luxurymentioning
confidence: 99%